The evolution of Eocene (Ypresian/Lutetian) sphenoliths: biostratigraphic implications and paleoceanographic significance from North Atlantic Site IODP U1410 - Cappelli, Carlotta; Bown, Paul R.; de Riu, Martina; Agnini, Claudia (Newsletters on Stratigraphy, 2021)
Sphenoliths are a diverse and evolutionarily dynamic group of Cenozoic nannofossils which are widely used in biostratigraphic and paleoecological studies. We document the early-middle Eocene evolutionary succession of sphenoliths from IODP Site U1410 in the NW Atlantic Ocean (Southeast Newfoundland Ridge). The exquisite nannofossil preservation at this site allows us to better delineate the morphologic and optical features of these sphenoliths and to document new fragile morphotypes. These include forms bearing long and fragile lateral processes (the ‘spiny sphenoliths’ group) that are the possible ancestors of the Sphenolithus furcatolithoides group, which is characterized by well-developed apical cycles and typically bifurcating spines. New quantitative stratigraphic analyses highlight the biostratigraphic potential of the S. furcatolithoides group throughout Zones NP14-NP15 (Martini 1971) and six key intervals characterized by shifting sphenolith assemblage compositions are identified through the early-middle Eocene. These are: 1) the post-EECO S. moriformis decrease, 2) the S. radians-S. spiniger turnover across the Ypresian-Lutetian transition, 3) the appearance and diversification of the ‘spiny sphenoliths’ group during the early Lutetian, and 4–6) development of the S. furcatolithoides evolutionary lineage, including S. pseudo-furcatolithoides (sp. nov., former S. furcatolithoides morphotype A), S. cuniculus, S. furcatolithoides (former S. furcatolithoides morphotype B) and S. strigosus. Assemblage compositions shifts and stable isotope records indicate possible environmental forcing on sphenolith evolution, suggesting the group is sensitive to changes in trophic and/or thermal conditions.